1
$\begingroup$

Let $\Gamma\cup\{\phi,\psi\}\subseteq L \epsilon$ then $\Gamma\models\psi$ if and only if $\Gamma,(\neg\phi)\models(\psi\land(\neg\psi))$. I don't seem to understand how the reverse implication goes. Can anyone help me out ? Thanks.

$\endgroup$
1
$\begingroup$

Written like this, it makes no sense. I assume you wanted to write

$$\Gamma\models\phi\text{ iff }\Gamma,\neg\phi\models\psi\land\neg\psi$$


To prove this, it is helpful to note that for $\Delta\cup\{\psi\}\subseteq\mathcal L_{FO}$, $\Delta\not\models\psi\land\neg\psi$ iff $\Delta$ is satisfiable, as then there is an interpretation $\mathcal I$ s.t. $\mathcal I\models\Delta$, and naturally $\mathcal I\not\models\psi\land\neg\psi$.

Now on to proving the equivalence. Let $\Gamma\cup\{\phi,\psi\}\subseteq\mathcal L_{FO}$.

From left to right, assume $\Gamma\models\phi$, i.e. for every interpretation $\mathcal I$: $\mathcal I\models\Gamma$ implies $\mathcal I\models\phi$. Thus, no interpretation $\mathcal I$ models $\Gamma,\neg\phi$ and thus for every interpretation $\mathcal I$: $\mathcal I\models\Gamma,\neg\phi$ implies $\mathcal I\models\psi\land\neg\psi$.

From right to left, assume $\Gamma\not\models\phi$, i.e. there is an interpretation $\mathcal I$ s.t. $\mathcal I\models\Gamma$ but $\mathcal I\not\models\phi$. The latter implies $\mathcal I\models\neg\phi$. Thus $\mathcal I\models\Gamma,\neg\phi$, i.e. $\Gamma,\neg\phi$ is satisfiable and thus $\Gamma,\neg\phi\not\models\psi\land\neg\psi$.

$\endgroup$
1
  • $\begingroup$ Ah yes thats what i meant , yes Thank you my friend ! $\endgroup$
    – Something
    Mar 30 '19 at 11:00

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.